IIUM cubeSat structural subsystem design - Isharuddin, Siti Sarah; Okasha, Mohamed; Ibrahim, Sultan (Trans Tech Publications Ltd., Switzerland, 2015)
This paper investigates the development process of a CubeSat model structure subsystem for the International Islamic University Malaysia (IIUM). Many universities around the world have participated in similar CubeSat Satellite projects. CubeSat satellite enables to design and produce a fully functional satellite at low cost compared to other types of satellites. It gives the engineering students especially the aerospace one, a hands-on education, and learning about how to design their own satellite. This paper will discuss the procedures that can be used to design and test the CubeSat structure subsystem considering design goals and constraints. The analyses will consider the structure static and vibration tests utilizing ANSYS Workbench platform and SolidWorks software and the simulation results will be compared with the experimental test results on the physical model.